Download presentation
Presentation is loading. Please wait.
1
The sum of any two even integers is even.
Theorem 3.1.1 The sum of any two even integers is even.
2
Proof: Suppose m and n are [particular but arbitrarily chosen] even integers. [We must show that m + n is even.] By definition of even, m = 2r and n = 2s for some integers r and s.
3
Proof continued: Then, m + n = 2r + 2s by substitution
= 2(r + s) by factoring out a 2 Let k = r + s. Note that k is an integer because it is a sum of integers. Hence m + n = 2k where k is an integer. It follows by definition of even that m + n is even. [This is what we needed to show]
4
Exam Question The sum of any even integer and any odd integer is odd.
5
Related Homework Problems
Section 3.1: 12, 13, 16, 17, 24 – 30.
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.